Keberagaman Gender dan Ukuran Direksi terhadap Nilai Perusahaan Properti - Nur Syarisma; Rahman Anshari; Muhammad Iqbal Pribadi (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the influence of gender diversity and the size of the board of directors on the value of companies in the property sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Company value is measured using the Price to Book Value (PBV) ratio. This research method is quantitative with a multiple linear regression approach. The sample consisted of 296 firm-year observations selected by purposive sampling technique. The results of the study show that gender diversity and the size of the board of directors do not have a significant effect on the company's value. This indicates that these two factors have not yet become the main consideration of the market in assessing the performance of property companies. This study contributes to the corporate governance literature and serves as a consideration for managers and regulators in formulating more inclusive policies.